Peluang dan Tantangan Transformasi Pelayanan Pemerintahan Desa Berbasis Digital di Riau - Nurmaini Dalimunthe; Nora Rosalia; Khairunsyah Purba (Yayasan Almanar Pujud, 2025)
Digital-based services have become an essential element in effective governance and the improvement of public service provision in the modern era. However, the adoption and implementation of digital services in rural areas face complex challenges. This study aims to identify and analyze the barriers hindering the implementation of digital services in Giti Village and Aliantan Village. A qualitative approach is used to explore the technical, organizational, social, and financial barriers affecting the application of technology in these areas. The research findings reveal that limited infrastructure, including unstable internet access and a lack of technological devices, are major obstacles. Additionally, issues of privacy and data security, resistance from organizations, and a lack of training and capacity-building for human resources also slow down the digital transformation process. Social factors, such as low digital literacy among the community, also influence the level of digital service adoption. This study emphasizes the importance of a holistic approach to overcoming these barriers through strengthening infrastructure, providing ongoing training, raising awareness about data security, and enhancing collaboration between the government and local stakeholders. By addressing these challenges, digital technology can be maximized to drive inclusive development and strengthen village governance in the future.